The McGill Transgenic Rat Model of Alzheimer's Disease Displays Cognitive and Motor Impairments, Changes in Anxiety and Social Behavior, and Altered Circadian Activity - Petrasek, Tomas; Vojtechova, Iveta; Lobellova, Veronika; Popelikova, Anna; Janikova, Martina; Brozka, Hana; Houdek, Pavel; Sladek, Martin; Sumova, Alena; Kristofikova, Zdenka; Vales, Karel; Stuchlík, Ales (Frontiers in Aging Neuroscience, 2018)
The McGill-R-Thy1-APP transgenic rat is an animal model of the familial form of Alzheimer's disease (AD). This model mirrors several neuropathological hallmarks of the disease, including the accumulation of beta-amyloid and the formation of amyloid plaques (in homozygous animals only), neuroinflammation and the gradual deterioration of cognitive functions even prior to plaque formation, although it lacks the tauopathy observed in human victims of AD. The goal of the present study was a thorough characterization of the homozygous model with emphasis on its face validity in several domains of behavior known to be affected in AD patients, including cognitive functions, motor coordination, emotionality, sociability, and circadian activity patterns. On the behavioral level, we found normal locomotor activity in spontaneous exploration, but problems with balance and gait coordination, increased anxiety and severely impaired spatial cognition in 4–7 month old homozygous animals. The profile of social behavior and ultrasonic communication was altered in the McGill rats, without a general social withdrawal. McGill rats also exhibited changes in circadian profile, with a shorter free-running period and increased total activity during the subjective night, without signs of sleep disturbances during the inactive phase. Expression of circadian clock gene Bmal1 was found to be increased in the parietal cortex and cerebellum, while Nr1d1 expression was not changed. The clock-controlled gene Prok2 expression was found to be elevated in the parietal cortex and hippocampus, which might have contributed to the observed changes in circadian phenotype. We conclude that the phenotype in the McGill rat model is not restricted to the cognitive domain, but also includes gait problems, changes in emotionality, social behavior, and circadian profiles. Our findings show that the model should be useful for the development of new therapeutic approaches targeting not only memory decline but also other symptoms decreasing the quality of life of AD patients.